Analisis Penerapan Preventive Maintenance Terhadap Performa Sistem Hidrolik Mesin Injection Moulding Model Ft 420 - Rahmat Nurhidayatul Ilmi; Dani Mardiyana; Oscar Haris (Universitas Nusa Putra, 2022)
Preventive maintenance is a maintenance activity that is carried out on a scheduled basis, this activity aims to find out the results of the analysis of the application of preventive maintenance on the hydraulic system on the FT 420 model injection molding machine, to know the performance of the hydraulic system from the application of preventive maintenance on injection molding machines on the FT 420 model injection molding machine. and find out the problems that occur before and after the application of preventive maintenance hydraulic system injection molding machine model FT 420. This research method includes activities of literature studies, field studies, problem identification, application of preventive maintenance, analysis of preventive maintenance testing and analysis of the results of applying preventive maintenance. With this application, it can be seen that the performance increase in injection molding machines is based on the data that has been obtained, namely if prior to this activity in the period December to May 2022 the average engine productivity only reached 85%, different after the implementation in April to June, namely as many as 96 % or increased by 6% while the down time rate of the machine before preventive maintenance in the same month period reached 90 different hours after this implementation experienced a significant decrease only 20 hours only. Therefore, this research will discuss the Analysis of the Application of Preventive Maintenance on the Performance of the Hydraulic System of the Injection Molding Machine Model FT 420